2021
DOI: 10.5937/fme2102494m
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between hybrid method technique and transfer matrix method for design optimization of vehicle muffler

Abstract: Hybrid mufflers are now commonly equipped to decrease vehicle noise and are a crucial tool for regulation of the acoustic system. In order to ensure optimum engine efficiency, the system is intended to dump the strength of the acoustic pulses generated from the engine, and the back pressure created by these systems must be held to a minimum. Typically, modern mufflers have a complex structure of chambers and flow paths. There are a number of mechanisms for sound dampening that operate to silence the sound flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The study's findings suggested that using sound-absorbing material could lower SPL by 15% to 20%. [13][14][15] For automotive engines, Vasiraja and Saravana Sathiya Prabhahar 16 designed a muffler with perforated inner pipes and nozzles to reduce the sound pressure level. The investigation looked at the effect of convergence angle and nozzle number.…”
Section: Introductionmentioning
confidence: 99%
“…The study's findings suggested that using sound-absorbing material could lower SPL by 15% to 20%. [13][14][15] For automotive engines, Vasiraja and Saravana Sathiya Prabhahar 16 designed a muffler with perforated inner pipes and nozzles to reduce the sound pressure level. The investigation looked at the effect of convergence angle and nozzle number.…”
Section: Introductionmentioning
confidence: 99%